Data analytics and management in data intensive domains : XVIII International Conference, DAMDID/RCDL 2016, Ershovo, Moscow, Russia, October 11-14, 2016, Revised selected papers /: XVIII International Conference, DAMDID/RCDL 2016, Ershovo, Moscow, Russia, October 11-14, 2016, Revised selected papers. (2017) - Unknown
No abstract available